Kvadratmeter per barn : ett planeringsverktyg som mäter kvalitet? - Normann-Bjarsell, Elin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2014)
Today's planning strategy, densification of cities, makes it difficult for municipal authorities to find spaces to build preschools and daycare centers on. The Planning and Building Act , Chapter 8, § 9 states that " if the site should be developed with buildings that contain one or more dwellings or premises for after-school , preschool, school or other activities, it should be on the property or near it, enough free space which is suitable for play and being outdoors. " Each municipality has to define the expression enough free space and a number of municipalities have established guidelines for preschool and daycare centers concerning dimensions. The guidelines measure the number of square meters of free space per child with the aim of contributing to a qualitative environment. But the size is just one quality and the issue is how other non-quantifiable qualities are taken into account in the planning process. The paper compares three municipalities, Gothenburg, Malmö and Lund. What guidelines have they implemented, why a certain size, and how do they take other qualities into account. The purpose of this paper is to problematize the concept of quality in planning for children in the urban context by exploring municipal guidelines for preschools and daycare centers. To understand the existing planning conditions, policy documents such as laws, regulations, ordinances and guidelines were studied. The municipalities were interviewed and because they rely on older guidelines as the basis for their current guidelines, a historical search of these documents was executed. The conclusion of the historical search is that the guidelines are based on practice and very little on scientific research. Observed in the study was how the guidelines usually is torn from their context, and that many are not aware of what the guidelines are based on and why they are a certain square feet. Considering planning practice, quantifiable guidelines are tradition but simplify the reality. Guidelines are necessary tools to render the planning process effective, but to create a more qualitative preschool and daycare center environments there is need for additional tools to highlight the so-called "soft", non-quantifiable values.